Risk Factors Associated with Adverse Events of Acupuncture: A Prospective Study. Issue 6 (December 2014) - Chung, Ka-Fai; Yeung, Wing-Fai; Kwok, Chi-Wa; Yu, Yee-Man
Objective: Mild adverse events (AEs) are common with acupuncture, but the risk factors remain unclear. A prospective study using a standardised AE assessment and acupuncture protocol was undertaken to address the question. Methods: A 20-item AE report form investigated local and systemic AEs in 150 adults with insomnia randomised to receive traditional, minimal and non-invasive sham acupuncture. Sociodemographic, clinical and psychological variables at baseline and past history and perceived credibility of acupuncture were assessed. Results: The incidence of any AEs per patient was 42.4% with traditional acupuncture, 40.7% with minimal acupuncture and 16.7% with non-invasive sham acupuncture. Traditional and minimal acupuncture were associated with a greater number of local AEs, while the presence of a chronic medical condition was predictive of fewer local and systemic AEs. Greater severity of insomnia, anxiety, depression, somatic symptoms and pain catastrophising thoughts were associated with lower risk, but most of the significant correlations disappeared after logistic regression. Divorce and widowhood were the only significant sociodemographic variables, while previous acupuncture treatment and perceived credibility of acupuncture were found to be unrelated. The risk of any AEs was higher in participants receiving traditional acupuncture (OR 4.26) and minimal acupuncture (OR 4.27) and in those without medical comorbidity (OR 3.39). Conclusions: The prevalence of AEs was higher than usual, probably due to the low threshold in our definition of AEs and the systematic collection from the patients' perspective. Baseline variables were largely unable to predict AEs associated with acupuncture. Further studies should explore the roles of practitioners, patients' anxiety during treatment and patient–practitioner interactions. Trial Registration Number: NCT01707706.